1997
DOI: 10.1172/jci119469
|View full text |Cite
|
Sign up to set email alerts
|

Role of ouabain-like compound in the rostral ventrolateral medulla in rats.

Abstract: To determine whether ouabain-like compound (OLC) exerts modulatory influences on the activity of vasomotor neurons in the rostral ventrolateral medulla (RVLM), we examined the effects of microinjecting ouabain, digoxin-specific antibody Fab fragments, and mAb against ouabain on the rat RVLM. Microinjection of ouabain into the unilateral RVLM of anesthetized normotensive rats elicited dose-dependent increases in mean arterial pressure (MAP) and renal sympathetic nerve activity (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 46 publications
1
10
0
1
Order By: Relevance
“…The sympathetic hyperactivity induced by ouabain and the consequent increase in blood pressure appear to involve the central renin-angiotensin system. This observation is supported by reports that the sympathetic hyperactivity induced by ouabain is prevented by an AT1 receptor blocker (50)(51)(52), suggesting that the central renin-angiotensin system could be the sympathoexcitatory component involved in the hypertensinogenic effect of ouabain. In addition, the acute hypertensinogenic effect of ouabain is attenuated in transgenic rats that are deficient in brain angiotensinogen (54).…”
Section: Acute Effects Of Ouabain On the Central Nervous Systemsupporting
confidence: 71%
See 1 more Smart Citation
“…The sympathetic hyperactivity induced by ouabain and the consequent increase in blood pressure appear to involve the central renin-angiotensin system. This observation is supported by reports that the sympathetic hyperactivity induced by ouabain is prevented by an AT1 receptor blocker (50)(51)(52), suggesting that the central renin-angiotensin system could be the sympathoexcitatory component involved in the hypertensinogenic effect of ouabain. In addition, the acute hypertensinogenic effect of ouabain is attenuated in transgenic rats that are deficient in brain angiotensinogen (54).…”
Section: Acute Effects Of Ouabain On the Central Nervous Systemsupporting
confidence: 71%
“…These effects of ouabain are due at least in part to activation of the central and peripheral renin-angiotensin system (31,28,(50)(51)(52).…”
Section: General Considerationsmentioning
confidence: 99%
“…37 The sympathoexcitatory and pressor responses to central infusion of aldosterone and Na + -rich aCSF can be prevented by central infusion of the sodium channel blocker benzamil or an ouabain blocker, 27,38 and the pressor responses elicited by central infusion of aldosterone or ouabain can be blocked by an AT 1 blocker. 27,39 In the RVLM, microinjection of an ouabain-like compound 40 or angiotensin II 21 elicits a pressor response and sympathoexcitation. Collectively, these data suggest that aldosterone in the RVLM might activate central mechanism(s) involving the MR-ENaC-ouabain pathway, thereby causing sympathetic hyperactivity and hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Although the exact chemical structure of this factor(s) is still debated, current evidence suggests that it is closely related to or identical to ouabain (Hamlyn et al, 1991), marinobufagenin , proscillardin A (Sich et al, 1996), or bufalin (Hilton et al, 1996). Digoxin-specific Fab has been shown to neutralize the effects of exogenous ouabain on central nervous system-mediated changes in blood pressure (Teruya et al, 1997), Rb uptake in erythrocytes (Balzan et al, 1991), and vascular smooth muscle contraction (Krep et al, 1995). Additional studies have shown that digoxin-specific Fab has the ability to neutralize an endogenous factor with Na ϩ /K ϩ ATPase inhibitory activity similar to ouabain produced in human peritoneal dialysate (Krep et al, 1995;Tao et al, 1996), cord blood of neonates (Balzan et al, 1991), and rat brain (Huang and Leenen, 1996).…”
Section: Discussionmentioning
confidence: 99%